A Qualitative Analysis of Students' Errors in Fraction Word Problems Based on Polya’s Stages of Problem Solving: Evidence from Papua, Indonesia - Hadiyanti, Yosefin Rianita; Manurung, Mayor M.H. (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2025)
This study investigates the types and causes of student errors in solving fraction word problems using Pólya’s four-step problem-solving framework: understanding the problem, devising a plan, carrying out the plan, and reviewing the solution. Employing a descriptive qualitative design, data were collected from three Grade VII students at SMP Negeri 2 Sentani, Papua, Indonesia, through written tests and semi-structured interviews. The findings reveal that students made errors at each stage of problem solving. Misidentification of known and unknown quantities, improper selection of operations, computational mistakes, and the absence of solution verification were frequently observed. These errors were attributed to weak conceptual understanding, limited procedural fluency, representational difficulties, and insufficient metacognitive awareness. Furthermore, cultural and contextual factors including linguistic challenges in interpreting mathematical terminology, classroom norms emphasizing speed over reflection, and limited exposure to diverse problem types contributed to students’ difficulties. The study suggests that mathematics instruction in similar educational settings should incorporate language support, structured scaffolding aligned with Pólya’s framework, and explicit metacognitive training to enhance students' problem-solving abilities.